(untitled) (Research, Society and Development, 2021)
Beach Tennis is currently a practice that has been growing a lot all over the world, especially because of the ease that a person learns to play and for the fun that it provides. Beach Tennis is a sport played on a sand court, with rules and execution of movements similar to those of tennis. With the recent arrival of the sport in the courts of Criciúma, this study aims to analyze the profile of beach tennis players in the city. descriptive quantitative research approach to analyze the data that were collected through a questionnaire with closed questions that was prepared in order to identify the profile of practitioners. Participated in the research 81 voluntary practitioners. It was concluded that the public who practices the sport in the city of Criciúma is composed mostly of female gender 75.3%, ages between 25 and 35 years. In level of education, 85.2% have higher education and 60.5% are married. Most of the practitioners are employees of private companies, businessmen, and liberal professionals have a monthly income above 3,500 reais (80.20%) and live in Criciúma (87.70%), in a distance between 1 to 4 km and all use a car as means of transportation. As for the characteristics of the training sessions, most train for 1 to 3 months (48.15%), they practice for recreation (59.26%), and because most of them are beginners in beach tennis they participate in category D (44.83%) in the championships and also 75.30% have their own racket and do not train only in beach tennis.